A Model of Calculating Radiative Opacities of Hot Dense Plasmas Based on the Density-Functional Theory. (2nd September 2014) - Kiyokawa, Shuji
Abstract : We determine the radiative opacity of plasmas in a local thermal equilibrium (LTE) by time-dependent density-functional theory (TDDFT) including autoionization resonances, where the photoabsorption cross section is calculated for an ion embedded in the plasma using the detailed configuration accounting (DCA) method. The abundance of ion with integer occupation numbers is determined by means of the finite temperature density-functional theory (FTDFT). For an Al plasma of temperatureT = 20  eV and density 0.01 g/cm 3, we show the opacity and the photoabsorption cross section of b-f and b-b transitions with Doppler and Stark width, and also show a result that the Planck and Rosseland mean opacities are 28, 348 cm 2 /g and 4, 279 cm 2 /g, respectively.